All Days 2007
DOI: 10.4043/18860-ms
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Studies on the Geomechanical Stability of Hydrate-Bearing Sediments

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThe thermal and mechanical loading of oceanic Hydrate-Bearing Sediments (HBS) can result in hydrate dissociation and a significant pressure increase, with potentially adverse consequences on the integrity and stability of the wellbore assembly, the HBS, and the bounding formations. The perception of HBS instability, coupled with insufficient knowledge of their geomechanical behavior and the absence of predictive capabilities, have resulted in a strategy of av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 11 publications
(21 reference statements)
3
68
0
Order By: Relevance
“…Geomechanical changes brought about by dissociation can have a significant impact on production, including porosity and permeability reduction (as the cementing hydrate dissociates, and more stresses are transferred to the generally unconsolidated sediments in HBS), subsidence, formation yielding/failure, and wellbore stability (Rutqvist and Moridis, 2007). It is possible that geomechanical considerations may prevent production from otherwise promising hydrate deposits if conventional oilfield technology is to be used.…”
Section: Gas Production Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Geomechanical changes brought about by dissociation can have a significant impact on production, including porosity and permeability reduction (as the cementing hydrate dissociates, and more stresses are transferred to the generally unconsolidated sediments in HBS), subsidence, formation yielding/failure, and wellbore stability (Rutqvist and Moridis, 2007). It is possible that geomechanical considerations may prevent production from otherwise promising hydrate deposits if conventional oilfield technology is to be used.…”
Section: Gas Production Strategiesmentioning
confidence: 99%
“…Such fractured-reservoir accumulations may be common in certain areas, with thick sections exhibiting massive vein fills, high concentrations of small hydrate nodules, smaller vein fills, or massive layers parallel to bedding planes . However, unlike the sand/sandstone systems where grain-supported reservoirs result in high matrix permeability and for which well-based production concepts are more plausible, extraction of methane from these shaleencased fractured accumulations is expected to be problematic because of significant geomechanical challenges that may affect the integrity of the formation and the well stability (Rutqvist and Moridis, 2007). Major technological advancements beyond current production systems will be needed before production from such deposits becomes feasible.…”
Section: Introductionmentioning
confidence: 99%
“…On the numerical model dealing with the deformation of hydrate-bearing sediments, Klar et al [26] studied the deformation of sediments containing gas hydrate and developed a geomechanical model in FLAC2D code to study the wellbore stability during hydrate dissociation induced by isothermal depressurization. Rutqvist and Moridis [27] proposed a numerical method by coupling the simulator TOUGH+HYDRATE with the geomechanical code FLAC3D and investigated the coupled thermal, hydraulic and geomechanical behaviors of hydrate deposits. Kimoto et al [28] investigated the deformation of ground induced by hydrate dissociation, the elastic-viscoplastic model was adopted to simulate the mechanical behavior of soil containing hydrate.…”
Section: Introductionmentioning
confidence: 99%
“…Using general principles of marine slope stability and fracture, Kleinberg (2005) showed that the presence and decomposition of hydrates in shallow marine sediments had the potential for fracturing and slope instability. Recent work has incorporated a geomechanical component in numerical simulations of hydrate reservoirs (Freij-Ayoub et al 2007, Rutqvist & Moridis 2007. Simulations show that warming due to pipelines and production can affect the cohesion and stability of hydrate-bearing sediment, especially for unconsolidated sediments that are typical near the sea floor.…”
Section: Figurementioning
confidence: 99%